Cutting characteristics of binderless diamond tools in high-speed turning of Ti-6Al-4Vp: – Availability of single-crystal and nano-polycrystalline diamond - Kamaruddin, A.M.N.A.; Hosokawa, A.; Furumoto, T.; Ueda, T. (Fuji Technology Press, 2016)
In this study, the tool performance of two types of binderless diamond tools – single-crystal diamond (SCD) and nano-polycrystalline diamond (NPD) – is investigated in the high-speed cutting of titanium alloy (Ti-6Al-4V) with a water-soluble coolant. The NPD tool allows for a larger cutting force than the SCD tool by dulling of the cutting edge, despite NPD being harder than SCD. This large cutting force and the very low thermal conductivity of NPD yield a high cutting temperature above 500°C, which promotes the adhesion of the workpiece to the tool face, thereby increasing tool wear. Based on the morphology of the tool edge without scratch marks and the elemental analysis by energy-dispersive X-ray spectroscopy (EDX) of both the flank face and the cutting chips, diffusiondissolution wear is determined to be the dominant mechanism in the diamond tool. A thin TiC layer seems to be formed in the boundary between the diamond tool and the titanium alloy at high temperatures; this is removed by the cutting chips.